Training Activity Program in Teacher Competency Development Marasa Ibtidaiyah - Mukhoiyaroh, Mukhoiyaroh; Mujiono, Mujiono; Mukaromah, Lailatul (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2025)
Competency development for teachers is a necessary task that every teacher should undertake. Teacher competency development is intended to enhance teachers' skills and support the smooth execution of tasks. MIN 1 Mojokerto can continue to a higher level of education, whether it is above the current level or the next, whether public or private. These skills are not spared by the teacher competency development training activities that have been provided to teachers, which then have a positive impact on the learning provided to students, resulting in increased learning outcomes. Based on the explanation above, the researcher developed the research title "Training Activity Program in Teacher Competency Development, Min 1 Mojokerto." With a research focus on the training in MIN 1 Mojokerto and how the training results are implemented. 1) What is the competence of the teachers at MIN 1 Mojokerto? 2) What is the program process for training activities at MIN 1 Mojokerto? Using a descriptive qualitative approach. This research yielded the following findings: Mojoketo MIN 1 teachers possess competencies in pedagogic, personality, and social competence. This result will be achieved through several achievement process activities undertaken by Mojokerto MIN 1 to improve teacher competence, namely: monthly performance evaluation, KKG training/MGMP, and Delegation of Training and Seminar Activities.